Analysis of Digital Tourist's Purchasing Decision Process Based on Feedback and Opinions - Kupi, Marcell; Bakó, Ferenc (Decision Making: Applications in Management and Engineering, 2024)
Today, tourism and digitalisation are very much intertwined. The phenomenon of tourism in the digital space - digital tourism - emerged with the birth of the internet and has grown in intensity over the years. The evolution of digitalisation has brought about a paradigm shift that has not only led consumers to adopt information and communication technologies, but has also greatly transformed consumer behaviour, preferences and motivations. Indeed, the development of technology has disrupted the traditional booking trends of tourists, their attitudes towards tourism and the social groups of tourists by providing dynamic online communication channels. Digital tourism users - digital tourists - are increasingly aware of the information and communication technologies, services and tools available to them, and are able to shape the market offer tailored to their needs through their actions and the data they provide. One of the most effective means of doing this is to share feedback and opinions online. In our research, I provide secondary information to support the importance of feedback and opinions, clarify its role in digital tourism, and then investigate the phenomenon of electronic-world-of-mouth through a questionnaire survey and decision tree analysis, and highlight the insights and implications of eWOM for digital tourists' behaviour in the online space based on opinions.